Saturated Iso-Type Fatty Acids from the Marine Bacterium Mesoflavibacter zeaxanthinifaciens with Anti-Trypanosomal Potential - Dayana Agnes Santos Ferreira; Erica Valadares de Castro Levatti; Lucas Monteiro Santa Cruz; Alan Roberto Costa; Álvaro E. Migotto; Amanda Yaeko Yamada; Carlos Henrique Camargo; Myron Christodoulides; João Henrique G. Lago; Andre Gustavo Tempone (MDPI AG, 2024)
Chagas disease is a Neglected Tropical Disease with limited and ineffective therapy. In a search for new anti-trypanosomal compounds, we investigated the potential of the metabolites from the bacteria living in the corals and sediments of the southeastern Brazilian coast. Three corals, Tubastraea coccinea, Mussismilia hispida, Madracis decactis, and sediments yielded 11 bacterial strains that were fully identified by MALDI-ToF/MS or gene sequencing, resulting in six genera-Vibrio, Shewanella, Mesoflavibacter, Halomonas, Bacillus, and Alteromonas. To conduct this study, EtOAc extracts were prepared and tested against Trypanosoma cruzi. The crude extracts showed IC50 values ranging from 15 to 51 μg/mL against the trypomastigotes. The bacterium Mesoflavibacter zeaxanthinifaciens was selected for fractionation, resulting in an active fraction (FII) with IC50 values of 17.7 μg/mL and 23.8 μg/mL against the trypomastigotes and amastigotes, respectively, with neither mammalian cytotoxicity nor hemolytic activity. Using an NMR and ESI-HRMS analysis, the FII revealed the presence of unsaturated iso-type fatty acids. Its lethal action was investigated, leading to a protein spectral profile of the parasite altered after treatment. The FII also induced a rapid permeabilization of the plasma membrane of the parasite, leading to cell death. These findings demonstrate that these unsaturated iso-type fatty acids are possible new hits against T. cruzi.